La Marginalité Du Genre Dans Les Grandes Agglomérations En Côte d’Ivoire : Le Cas De La Prostitution De Luxe À Abidjan - Denis, M. Gueu (European Scientific Journal, ESJ, 2016)
This study aims to understand and explain the phenomenon of luxury prostitution in Abidjan, to propose solutions. The research took place in the municipalities of Cocody and Marcory and were based on 30 participants. This is direct actors, including several prostitutes, their clients and indirect stakeholders such as the populations of these towns, some relatives and acquaintances of prostitutes and some structures’ officials concerned, from which diverse information was collected. Data were collected using a literature review and questionnaires and then analyzed quantitatively and qualitatively. The results certainly indicate that several factors, namely, the crisis of the family unit, lack of employment, bad companions realize the luxury prostitution in Abidjan, but the most prominent is poverty. These factors resulting disastrous consequences, such as sexually transmitted diseases and HIV / AIDS to name a few.